1999
DOI: 10.1103/physreve.60.6610
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of thermal conductivity on discrete breathers in lattices

Abstract: We study the properties of heat conduction in chains of coupled particles subjected to different anharmonic on-site potentials. Particular emphasis is placed on the role of breathers in saturation of the thermal conductivity for chains with hard anharmonicity. When the chain particles are subject to on-site potentials with soft anharmonicity, we find a characteristic temperature, below which the conductivity decreases but while above which it increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 16 publications
2
80
1
Order By: Relevance
“…A suggested picture to support this viewpoint is that the on-site potentials which destroy the conservation of momentum can induce a strong scattering mechanism for phonons, eventually resulting in the diffusive Fourier's heat transport. In some literature [60,61], such scattering mechanism is usually attributed to DBs. Nevertheless, at present, our understanding of the physical picture of this scattering process is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A suggested picture to support this viewpoint is that the on-site potentials which destroy the conservation of momentum can induce a strong scattering mechanism for phonons, eventually resulting in the diffusive Fourier's heat transport. In some literature [60,61], such scattering mechanism is usually attributed to DBs. Nevertheless, at present, our understanding of the physical picture of this scattering process is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This was done as nonlinear excitations are known to be generated from randomness [10,[36][37][38][39]. As the outcome of collisions between nonlinear excitations depends strongly on their relative phases, we made 500 different random initial conditions to be able to find effects independent of the random phases.…”
Section: ͑7͒mentioning
confidence: 99%
“…[10,12,[35][36][37][38][39], for example. In these references it was shown that solitons or discrete breathers can be generated from or exist among random thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of configurational defects 24,25,39 or disorder 9,15,25,31,40 in harmonic systems can also lead to diffusive transport, with the build up of a temperature gradient across the system. Defects and disorder introduce some form of localisation of the vibration modes 27,28 which do not favour ballistic transport 27 .…”
Section: Introductionmentioning
confidence: 99%